Pesticides Abuse and Health Implications in Ghana: A Review - Aidoo, Atta Kwesi; Arthur, Stephen; Arku, Grace Bolfrey –; Mochiah, Moses Brandford (International Journal of Environment, Agriculture and Biotechnology, 2019)
It is estimated that 25% of the globally produced pesticides are used in developing countries and African farmers use only 4%. However, more than 90% of the global minimum of 300,000 death cases related to pesticides poisoning annually are believed to occur in developing countries. Efforts have been made worldwide to restrict or ban the use of persistent pesticides while regulating the use of other pesticides to ensure environmental and food safety. However, most pesticide dealers and users of many developing countries including Ghana have not come to terms with the associated safety practices that ensure a safe use to keep the integrity of our environment. Pesticide residues have been detected in food, water, water sediment, air, blood and human breastmilk because of pesticide abuses. This paper reviews some abuse practices during handling and storage, application, or disposal; associated exposures; public health risks associated with the abuse practices; as well as issues of monitoring and enforcement. Some instances of casualties are also discussed.